2020
DOI: 10.3390/w12071999
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment of Water Resources in Beijing

Abstract: A sustainability assessment of water resources is essential for maintaining regional sustainable development. In this study, a comprehensive assessment of changes in the sustainability of the water resource system in Beijing from 2008 to 2018 was conducted on the basis of the driver-pressure-state-impact-response (DPSIR) model. To reflect the impacts of humans on the water consumption and pollution of water resources, the water footprint was considered. In addition, key factors that affect the sustainability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…What can be inferred from Figure 9 is that the lake ecosystem resilience is falling away from its natural state due to increasing rates of drivers, pressures, states, and impactsan indicator of the lake ecosystem's deterioration. Similar scenarios have been reported in China [100], New Zealand [101], and the Mekong river in China, Myanmar, Thailand, Lao PDR, Cambodia, and Vietnam [102]. The effect of demographic, socio-economic, and climatic factors as drivers, pressures, and environmental states were significant (p < 0.05) and negative, suggesting that these indicators negatively influenced the lake ecosystem resilience and contributed to its degradation.…”
Section: Lake Malombe Ecosystem Resilience and Influencing Factorsupporting
confidence: 72%
“…What can be inferred from Figure 9 is that the lake ecosystem resilience is falling away from its natural state due to increasing rates of drivers, pressures, states, and impactsan indicator of the lake ecosystem's deterioration. Similar scenarios have been reported in China [100], New Zealand [101], and the Mekong river in China, Myanmar, Thailand, Lao PDR, Cambodia, and Vietnam [102]. The effect of demographic, socio-economic, and climatic factors as drivers, pressures, and environmental states were significant (p < 0.05) and negative, suggesting that these indicators negatively influenced the lake ecosystem resilience and contributed to its degradation.…”
Section: Lake Malombe Ecosystem Resilience and Influencing Factorsupporting
confidence: 72%
“…This threshold was usually subjectively chosen in the literature. The subjective choice of varied from study to study, some of the choices are 0.55 [ 39 ], 0.6 [ 40 ], and 0.7 [ 41 ]. In our paper, we showed that this subjectivity would lead to inconsistent and even opposite conclusions in water resources evaluation and is prone to errors ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recommended that be taken in [0.5, 0.7] [ 58 , 59 , 89 ]. This threshold parameter is often subjectively chosen in this range of [0.5, 0.7] in the previous literature [ 38 , 39 , 40 , 41 ]. For a selected , the evaluation security rating is selected as the minimal k such that is greater than .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations